A survey of definitions of small business in the southern African context - A. P. Du Plessis; C. Boshoff; P. L. Moolman; G. Radder (South African Journal of Business Management, 1989)
This paper reports on a survey of the definition of small business as perceived by various organizations involved in small business training and development. Participants were requested to define small business in terms of quantitative as well as qualitative criteria. The definitions provided by the survey respondents were compared with published definitions of small business as formulated by the Small Business Development Corporation (SBDC), the National Manpower Commission (NMC), J.G. Smith (one of the first authors who attempted to define small business), and the Small Business Advisory Bureau (SBAB). The definitions suggested by respondents indicate a lack of definitional consensus. Although no specific definition is suggested here, it is hoped that the information provided and the interpretation thereof may stimulate and encourage efforts to formulate a simple, useful, and widely accepted definition of small business in southern Africa.
Keywords: 650